Civil society and freemasonry in the city of Zacatecas (1959-1977) - Gutiérrez Rojas, César Eduardo (2020)
The concept of civil society was classified as pro-democratic and pigeonholed for NGO’s and OSC’s, conditioning its interpretation. A similar situation was the conceptual link with the dissident political groups of the Mexican government from 1950 to 1970, as a consequence of the authoritarian-corporate context and the political-partisan restrictions, causing the use of civilian masks to carry out their agendas. Both positions nullified other possibilities of analysis, which is the reason for the importance of our research, thus a concept stemmed from ideological debates, identifying in the Masonic association of the city of Zacatecas a proposal to develop civil society.